2022
DOI: 10.3390/en15238808
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Simulation Investigation of Performance of Scaled Model for a Rotor of a Savonius Wind Turbine

Abstract: Renewable energy sources are preferred for many power generation applications. Energy from the wind is one of the fastest-expanding kinds of sustainable energy, and it is essential in preventing potential energy issues in the foreseeable future. One pertinent issue is the many geometrical alterations that the scientific community has suggested to enhance rotor performance features. Hence, to address the challenge of developing a model that resolves these problems, the purpose of this investigation was to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…In their study, Al-Gburi et al examined the characteristics of an elliptical blade profile with an inner wavy region, overlap ratio of 0.109, and a configuration consisting of two blades. The present investigation exhibited the maximum power coefficient [36]. Due to limited discussions on applying surface roughness, texture, or a wavy pattern to the semi-circular concave of the Savonius rotor for enhancing its performance, surface roughness emerges as a method that may be used to increase the drag force on the concave area.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…In their study, Al-Gburi et al examined the characteristics of an elliptical blade profile with an inner wavy region, overlap ratio of 0.109, and a configuration consisting of two blades. The present investigation exhibited the maximum power coefficient [36]. Due to limited discussions on applying surface roughness, texture, or a wavy pattern to the semi-circular concave of the Savonius rotor for enhancing its performance, surface roughness emerges as a method that may be used to increase the drag force on the concave area.…”
Section: Introductionmentioning
confidence: 74%
“…The external devices were intended to boost power, static torque, and self-starting capabilities [31]. The Savonius turbine harnesses disparities in the drag forces generated by the convex and concave sides of its rotor blades during spinning around a vertical shaft [32] [33]. By improving the drag force on the concave surface and reducing the drag force on the convex surface, it is possible to increase the disparity in the total amount of drag force that is produced using this method.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings, which demonstrate favorable performance compared to similar investigations on Savonius Drag-Type Vertical Wind Turbines, align well with the literature. Specifically, Gerrie et al [11] reported Cp values ranging from 0.12 to 0.14, Al-Gburi et al [15] reported a range from 0.10 to 0.21, Mohamed et al [21] reported a range from 0.10 to 0.25, Shukla et al [14] reported a range from 0.23 to 0.27, and Alom et al [41] reported a range from 0.11 to 0.33. However, it is crucial to acknowledge that each study involves a unique geometry, conditions, and experimental setups, which can influence the observed outcomes.…”
Section: Validity Of the Resultsmentioning
confidence: 99%
“…A number of other publications [12][13][14][15][16][17][18][19][20][21] have also focused on improving the performance of either Savonius, Daerius, or hybrid VAWTs using different approaches in design. However, it is important to note that while these turbines are practical for harnessing wind energy at low altitudes, the total energy produced is relatively low.…”
Section: Literature Surveymentioning
confidence: 99%
“…In this wind network, the modern turbines with very low specifc ratings plus high hub heights increase the wind energy potential. As a result, the overall wind power system installation cost is reduced [3]. Here, the wind turbines capture the wind velocity for running the dual-fed induction machine.…”
Section: Introductionmentioning
confidence: 99%